Appraising Quality of Nursing Practices in the Medical and Surgical Wards of Public Hospitals in Erbil City - Zhyan Abdulla Esmael; Namir Ghanim Al-Tawil (Hawler Medical University, 2020)
Background and objectives: Appraising the quality of nursing practices is a cornerstone for improving the nursing services. The objective of the study was to appraise the quality of nursing care provided to patients in the medical and surgical wards Methods: A cross-sectional study was conducted in the medical and surgical wards of Hawler, Rizgary, and the Maternity Teaching Hospitals located in Erbil city, Kurdistan region of Iraq, starting from December 17, 2016, until September 30, 2017. The researcher used to visit the hospital wards four days per week in order to monitor the nursing practices using a questionnaire adapted from the WHO. All the nurses were included in the study except for those who were not present during the researcher's visit. Data were analyzed by the SPSS program, and a p-value of less than 0.05 was considered significant. Results: Only 37.8% of the nurses performed assignments in a good manner, and none performed assignments in a very good manner. Nearly all the nurses performed poorly in the following areas: disposal of soiled linen promptly; ventilation and adequate lighting in the ward; cleanliness in ward/room; hand washing before and after patient treatment; and observation rules and upholding standards. Results showed that 52.7% of nurses showed a genuine interest in the comfort and health improvements of patients. Conclusions: The performance of nurses working in Erbil public hospitals was, in general, not so satisfactory (fair). It is recommended to engage the nurses in courses of continuing professional development (CPD) and to set standards for nursing care in the mentioned hospitals.